3D Hybrid Nanofiber Aerogels Combining with Nanoparticles Made of a Biocleavable and Targeting Polycation and MiR‐26a for Bone Repair. (9th September 2020) - Li, Ruiquan; Wang, Hongjun; John, Johnson V.; Song, Haiqing; Teusink, Matthew J.; Xie, Jingwei
Abstract: The healing of large bone defects represents a clinical challenge, often requiring some form of grafting. 3D nanofiber aerogels could be a promising bone graft due to their biomimetic morphology and controlled porous structures and composition. miR‐26a has been reported to induce the differentiation of bone marrow‐derived mesenchymal stem cells (BMSCs) and facilitate bone formation. Introducing miR‐26a with a suitable polymeric vector targeting BMSCs could improve and enhance the functions of 3D nanofiber aerogels for bone regeneration. Herein, the comb‐shaped polycation (HA–SS–PGEA) is first developed, carrying a targeting component, biocleavable groups, and short ethanolamine (EA)‐decorated poly(glycidyl methacrylate) (PGMA) (abbreviated as PGEA) arms as miR‐26a delivery vector. Thereafter, the cytotoxicity and transfection efficiency of this polycation and cellular response to miR‐26a‐incorporated nanoparticles (NPs) are assessed in vitro. HA–SS–PGEA exhibits a stronger ability to transport miR‐26a and exert its functions than the gold standard polyethyleneimine (PEI) and low‐molecular‐weight linear PGEA. The efficacy of HA–SS–PGEA/miR‐26a NPs loaded 3D hybrid nanofiber aerogels showing a positive effect on the cranial bone defect healing is finally examined. Together, the combination of 3D nanofiber aerogels and functional NPs consisting of a biodegradable and targeting polycation and therapeutic miRNA could be a promising approach for bone regeneration. Abstract : Combining 3D nanofiber aerogels with nanoparticles consisting of reducible polycation HA–SS–PGEA and miR‐26a is effective for cranial bone regeneration. The aerogels with biomimetic nanofibrous morphology and interconnected pores are ideal for stem cell adhesion and ingrowth. The HA–SS–PGEA protects miR‐26a against premature enzymolysis and enhances miR‐26a expression in stem cells, resulting in promotion of osteogenesis and angiogenesis.